Forest eternal? Endemic butterflies of the Bamenda Highlands, Cameroon, avoid close-canopy forest - Tropek, Robert (Jihočeská univerzita, 2008)
I studied habitat preferences of three common endemic butterflies in the Bamenda Highlands, Cameroon. Assuming that the life history traits of taxa with limited geographic distribution reflect past habitat conditions within their ranges, the history and conservation of West African mountain landscape is discussed.
Forest eternal? Endemic butterflies of the Bamenda Highlands, Cameroon, avoid close-canopy forest
Keywords: Afromontane landscape; conservation; habitat preferences; landscape heterogeneity; Lepidoptera; mountain forest history; sparse canopy; West Africa; Afromontane landscape; conservation; habitat preferences; landscape heterogeneity; Lepidoptera; mountain forest history; sparse canopy; West Africa